2023
DOI: 10.2147/idr.s393195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Six Patients with Chlamydia psittaci Infection Diagnosed by Metagenomic Next-Generation Sequencing: A Case Series

Abstract: The incidence of psittacosis infection has gradually increased in recent years. Metagenomic next-generation sequencing (mNGS) can be used to comprehensively identify the total DNA and RNA content of the microbiome, as well as identify both known and unexpected pathogens within 24 hours. We diagnosed and treated six patients with psittacosis infection using mNGS, two of whom developed severe disease and most of whom presented with pulmonary symptoms. One of the young female patients also presented with irregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similar to PCR, metagenomic data from next generation sequencing (mNGS) has higher sensitivity and is faster than culture [ 53 ]. Metagenomics data has successfully been used to identify C. psittaci cases within 24 h [ 78 ]. Given the potential ability to find evidence of C. psittaci infection from NGS versus a negative serological test, NGS use has been referred to as ‘hypothesis-free pathogen detection’ [ 79 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Similar to PCR, metagenomic data from next generation sequencing (mNGS) has higher sensitivity and is faster than culture [ 53 ]. Metagenomics data has successfully been used to identify C. psittaci cases within 24 h [ 78 ]. Given the potential ability to find evidence of C. psittaci infection from NGS versus a negative serological test, NGS use has been referred to as ‘hypothesis-free pathogen detection’ [ 79 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…The clinical features of Chlamydia psittaci infection are generally nonspecific. However, there have been reports of yellow-white sputum production in a minority of cases of Chlamydia psittaci pneumonia [ 3 5 ]. Research has demonstrated that the color of sputum can serve as a significant predictor of potentially pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, these bacteria were associated with only avian psittacosis [4][5][6]. However, since then it has been clearly proven that C. psittaci is also responsible for airway inflammation and reproductive disorders in cattle, small ruminants, domestic animals and humans [7][8][9][10][11][12][13]. C. psittaci (ovis), which is now re-classified to Chlamydia abortus, is responsible for abortion, stillbirth or fetal loss in ruminants worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, since then it has been clearly proven that C . psittaci is also responsible for airway inflammation and reproductive disorders in cattle, small ruminants, domestic animals and humans [ 7 13 ]. C .…”
Section: Introductionmentioning
confidence: 99%